PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN DAN REPUTASI KAP TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN - Yuniarti, Rina (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
The relevant and good financial report have the role to minimize the needs conflicts between companies and common stock holder and able to increase the value of companies and the common stock holder itself. The timeliness is an important factor in presenting an relevant information. This research is aimed to know the influence of liquidity, company scale and the reputation of Public Accountant Office (KAP) toward the timeliness of financial report. The population of this research are cigarretes and cosmetics companies which are listed in Indonesia Stock Exchange consist of six companies. The sample in this research was taken by using purposive sampling technique. The method in analyzing the data used in this research was a regression logistic test. The results of this research showed that the liquidity did not influence the timeliness of financial report. The company scale influence the timeliness of financial report. The reputation of Public Accountant Office (KAP) influence the timeliness of financial report.Keywords: Timeliness, Liquidity, Company Scale, Reputation of Public Accountant Office (KAP)